A 15 ka pH record from an alpine lake in north China derived from the cyclization ratio index of aquatic brGDGTs and its paleoclimatic significance. (July 2017) - Cao, Jiantao; Rao, Zhiguo; Jia, Guodong; Xu, Qinghai; Chen, Fahu
Highlights: brGDGTs in the sediments of Gonghai Lake are mainly of in situ aquatic origin. A CBT-derived pH record from Gonghai Lake reflects the lake water pH history. The lake water pH responded mainly to variation in summer monsoon intensity. Abstract: A well-dated sediment core from an alpine lake in north China (Gonghai Lake) was used for analysis of branched glycerol dialkyl glycerol tetraether lipids (brGDGTs). Based on the cyclization ratio index (CBT) of the brGDGTs, and using different terrestrial and lacustrine CBT-pH empirical relationships, the reconstructed pH records over the past ca. 15 ka exhibited similar trends of variation, although the absolute pH values were different. In order to better understand the reconstructed pH record, samples of surface soils from the dust source area and the catchment of Gonghai Lake, as well as surface sediments from the lake, were collected for instrumental pH measurements and modern brGDGT analysis. The instrumental pH results demonstrated that the surface soils from the dust source area were alkaline, while those from the catchment of Gonghai Lake were acidic. In addition, the instrumental pH results for the surface sediments from the lake were slightly alkaline and the corresponding pH values were intermediate between those of the two surface soil source groups. This may reflect the effect of the input of material from different sources on the sedimentary pH record. However, the results from modern brGDGTs in some of the surface soils and surface sediment samples demonstrate that brGDGTs in the core sediments from Gonghai Lake are predominantly of aquatic origin. Therefore, the CBT-derived pH record over the past ca. 15 ka from the lake can be interpreted as a record of the lake water pH history, which is consistent with the carbonate content record from a parallel core from the same lake. In addition, using the modern lacustrine calibration, the CBT-derived pH values for surface sediments of Gonghai Lake are consistent with instrumental modern lake water pH values for the lake. Further comparison indicates that the lake water pH is controlled mainly by the degree of humidity of the local climate, which is closely related to the intensity of the East Asian summer monsoon (EASM); therefore, the pH record can be used as an indicator of EASM intensity. Our results demonstrate that, on the basis of careful analysis of its origins, the CBT index of aquatic brGDGTs can be used for lake water pH reconstruction and subsequent paleoclimate reconstruction, and that in north China, the lake water pH is controlled mainly by the degree of humidity of the local climate.